LAYANAN PEMBERDAYAAN PEREMPUAN DAN ANAK PADA PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK “CITRA TEPIAN” KOTA SAMARINDA - Oktovianus Kondorura; Sutadji Sutadji; Fajar Apriani (Jurnal Administrative Reform, 2021)
The research objectives were to determine the type of service, analyze and identify supporting factors and inhibiting factors for empowerment services for women and children in Samarinda City. With this type of qualitative research. Data collection techniques are observation, interviews and documentation. Then the interactive model data analysis technique. The results of research on empowerment services for women and children at the Integrated Service Center for Empowerment of Women and Children "Citra Tepian" Kota Samarinda include the provision of information and data collection services through hotline calls or through the SIPPEKA application. Medical and psychological referral services are carried out in collaboration with hospitals and HIMPSI, legal aid services are provided for victims of women and child violence from the police office to the court and in the mediation stage. Safe home services to provide protection for victims. Supporting factors for empowerment services for women and children at the Integrated Service Center for Empowerment of Women and Children "Citra Tepian" Kota Samarinda, namely the existence of an application, namely the SIPPEKA application, while the inhibiting factors are the lack of human resource availability, lack of facilities and infrastructure and lack of budget support.Keywords: Women's and Children’s Empowerment Services, Integrated Service Centers